The indigo heiress [large type] - Frantz, Laura (Thorndike Press Large Print, 2025)
"To settle her family's debts and secure a suitable marriage for her sister, a colonial American indigo heiress is forced to wed a Scottish merchant she loathes. Leaving all she's ever known, she sails to Scotland to enter the complex world of the powerful Buchanan clan who are anything but what they seem"--